Inovasi Penilaian Maharah al-Qira’ah pada Buku Teks Bahasa Arab Berdasarkan Penilaian HOTS - Azzahra, Luthfi Qolbi; Baroroh, R Umi (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose- This research aimed to analyze tests based on higher-order thinking skills (HOTS) in assessing reading skills, as well as the innovations contained in the form of HOTS-based question development and variations in teaching techniques within the Arabic language textbook for grade X published by the Ministry of Religious Affairs in 2020. Design/Methodology/Approach- This research employed a library research method with a content analysis approach. The primary data source was the Arabic language textbook for grade X, while secondary data were obtained from relevant studies. Findings— The study found that the Arabic textbook for grade X published by the Ministry of Religious Affairs included six types of HOTS-based questions, though they were still limited. This research identified nine HOTS instruments, seven of which were new, such as identifying main ideas, analyzing information, evaluating ideas, and generating new ideas. These innovations were designed to support the development of Arabic reading skills. Research Limitation/Implications- This research was limited to a theoretical analysis of the 2020 Arabic Language textbook for grade X from the Ministry of Religious Affairs without field testing. However, this research served as an initial step in assessing the implementation of HOTS in Arabic language learning.